Governing Epidemics as Disasters Through Law: Lessons from COVID-19 in Assessing Tanzania’s Public Health and Disaster Management Frameworks - Temba, Ferdinand (Journal of Policy and Leadership, 2026)
This article analyses how Tanzania's legal and institutional frameworks shaped the management of epidemics as disasters during the COVID-19 pandemic. Focusing on the Public Health Act, 2009, and the Disaster Management Act No. 6 of 2022, the study applies doctrinal legal analysis and riskgovernance concepts to examine statutory mandates, policy instruments, and institutional practice. The findings show that the Public Health Act provided a clear legal basis for disease surveillance, quarantine, isolation, and control, while the Disaster Management Act established a multisectoral coordination framework. However, implementation gaps constrained their effectiveness. Despite the presence of supporting policy instruments, including the National Disaster Management Strategy (2022–2027) and the Tanzania Emergency Preparedness and Response Plan, epidemic governance was weakened by the absence of a formal disaster declaration, reliance on non-binding standard operating procedures, uneven inter-institutional coordination, and persistent inequalities in access to public health services. Although the disaster framework mandates institutional coordination, mainstreaming of disaster risk reduction, and community-based disaster management, these mechanisms were only partially realised during the pandemic. Nevertheless, the legal framework enabled rapid public health interventions and supported elements of a multisectoral response during a complex and evolving emergency. The article argues that Tanzania's epidemic preparedness can be strengthened through closer harmonisation of statutes and policy instruments, codification of operational guidelines, clearer disaster activation thresholds, integration of digital monitoring systems, and the embedding of rights-based safeguards. Therefore, the study underscores the importance of legal preparedness in strengthening disaster risk governance and resilience to future epidemics.